Impact of technologically processed rapeseeds on the content of glucosinolates - Mykytyn, Mykola; Melnyk, Uliana; Volchovska-Kozak Оleksandra (ScienceRise: Biological Science, 2019)
The purpose of the study is to determine the content of glucosinolates in rapeseed and its processing products, depending on the technological methods of its processing at different processing plants. Materials and methods. The studies were conducted using marketable rapeseed seeds, as well as by-products of its processing into oil - meal and cake. Samples of the initial and final products of processing were selected at those enterprises of Ukraine, which in the last few years have been engaged in processing rapeseed. The biochemical analysis of samples of seeds, meal and cake was performed by known methods. Calculated and analytical research methods were used to analyze the results obtained. Results. The studies have shown that reducing the content of glucosinolates also occurs in the process of industrial processing of commercial rapeseed oil. In the case of oil extraction enterprises, this figure is reduced by 50%, and in enterprises where there are no stages of extraction and toasting - by 25%. The analysis showed that the content of glucosinolates in domestic products of processing rapeseed (cake, meal) at this stage is an average of 25 μmol/g. However, this level is still higher than what is thought to be used in feeding monogastric animals without restriction, since then the content of glucosinolates in these products should not exceed 20 μmol/g. Conclusions. The content of the main anti-nutrients in rapeseed meal/cake of domestic production in the current year was 25,1-25,8 µmol/g d.m., which is still higher than the level that allows to use these products of processing rapeseed in feeding monogastric animals without limits